2019
DOI: 10.1038/s41477-019-0469-x
|View full text |Cite
|
Sign up to set email alerts
|

Mediation of plant–mycorrhizal interaction by a lectin receptor-like kinase

Abstract: The molecular mechanisms underlying mycorrhizal symbioses, the most ubiquitous and impactful mutualistic plant-microbial interaction in nature, are largely unknown. Through genetic mapping, re-sequencing and molecular validation, we demonstrate that a G-type lectin receptor-like kinase mediates the symbiotic interaction between Populus and ectomycorrhizal fungus Laccaria bicolor. This finding uncovers an important molecular step in the establishment of symbiotic plant-fungal associations and provides a molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 27 publications
0
44
0
Order By: Relevance
“…The coexpressed gene Potri.006G049600 encodes concanavalin A-like lectin protein kinase family protein that is involved in amino acid phosphorylation. Lectin receptor-like kinases ( LecRLK) are known to regulate abiotic and biotic stresses, and development in plants ( Vaid et al, 2013 ; Yang et al, 2016 ; Labbe et al, 2019 ). A comethylated gene with a similar function as the anchor genes is Potri.006G137100, which encodes a pectin lyase-like superfamily protein that functions in pectin methylesterase ( PME ) activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The coexpressed gene Potri.006G049600 encodes concanavalin A-like lectin protein kinase family protein that is involved in amino acid phosphorylation. Lectin receptor-like kinases ( LecRLK) are known to regulate abiotic and biotic stresses, and development in plants ( Vaid et al, 2013 ; Yang et al, 2016 ; Labbe et al, 2019 ). A comethylated gene with a similar function as the anchor genes is Potri.006G137100, which encodes a pectin lyase-like superfamily protein that functions in pectin methylesterase ( PME ) activity.…”
Section: Discussionmentioning
confidence: 99%
“…Wood traits are generally heritable (Carlquist, 2012) and serve as useful traits in phylogenetic analyses (Hietz et al, 2017). Radial variation in wood anatomical properties in the stem affects wood functional traits such as hydraulic conductivity and often scales with tree size and leaf characteristics (Lachenbruch et al, 2011). Genome-wide association studies of wood anatomy traits undoubtedly complement the current understanding of genetic architecture of other structural and functional traits in Populus and will serve as an important step for optimizing traits suitable for lignocellulosic biofuels.…”
Section: Introductionmentioning
confidence: 99%
“…Whether the kinase domain is required for its Nod factor binding capability and whether MtLecRK1;1 can bind to Nod factors require further protein-protein interaction studies to clarify. Moreover, a G-type LecRLK in Populus, PtLecRLK1, has recently been identified as a key player in the Populus-L. bicolor symbiosis (Labbe et al, 2019). The transcriptomic study has shown the transcriptional induction of PtLecRLK1 by L. bicolor and overexpression of PtLecRLK1 in Arabidopsis, which is a non-host for L. bicolor, could initiate the symbiosis between L. bicolor and Arabidopsis (Labbe et al, 2019).…”
Section: Lecrlks In Plant-microbe Symbiosismentioning
confidence: 99%
“…Moreover, a G-type LecRLK in Populus, PtLecRLK1, has recently been identified as a key player in the Populus-L. bicolor symbiosis (Labbe et al, 2019). The transcriptomic study has shown the transcriptional induction of PtLecRLK1 by L. bicolor and overexpression of PtLecRLK1 in Arabidopsis, which is a non-host for L. bicolor, could initiate the symbiosis between L. bicolor and Arabidopsis (Labbe et al, 2019). Although further studies are required to disclose the fungi signal perception and downstream targets and signaling responses mediated by PtLecRLK1, these findings demonstrated the key status of LecRLKs in host-fungi compatibility and provided insights on the further application of beneficial ectomycorrhizal fungi to crops.…”
Section: Lecrlks In Plant-microbe Symbiosismentioning
confidence: 99%
“…For example, a LecRK from Pisum sativum can enhance salinity stress tolerance of transgenic tobacco by alleviating the ionic and osmotic components of salinity stress [14]. In addition, G-type RKs mediate the symbiotic interaction between the ectomycorrhizal fungus Laccaria bicolor and Populus, which provides a stepping stone for the further study of plant-mycorrhizal interaction [17]. Taking all the above into consideration, the LecRK is a multi-talented family, which is waiting for us to explore its potential and underpin crop improvement for biotic resistance and abiotic tolerance.…”
Section: Introductionmentioning
confidence: 99%